Full silicone interpenetrating bi-networks with different organic groups attached to the silicon atoms. (23rd October 2015) - Tugui, Codrin; Cazacu, Maria; Sacarescu, Liviu; Bele, Adrian; Stiubianu, George; Ursu, Cristian; Racles, Carmen
Abstract: Mixed silicone interpenetrating networks have been prepared using two groups of siloxane polymers and copolymers as precursors in different combinations. Each combination chosen, after a good mixing in solution with cross-linking agents was processed into film, which has been stabilized through sequential crosslinking using separate chemical pathways: condensation with tetraethyl orthosilicate at room temperature for the first network and addition (hydrosilylation) at higher temperatures in the case of the second one. The morphology of the resulted materials was studied by scanning electron microscopy (SEM). The mixing degrees of the two networks were estimated on the basis of the differential scanning calorimetry (DSC) traces as well as by small angle X-ray scattering (SAXS). The obtained films were characterized from point of view of the properties of interest for electromechanical applications by mechanical testing, dielectric spectroscopy and electrical breakdown measurements. The influence of the nature and content of the polar groups attached on the silicon on these characteristics was discussed. Graphical abstract: Highlights: Dielectric elastomers based on silicone interpenetrated networks (IPNs) were prepared. Polar groups were attached to one of the networks to raise the dielectric permittivity. The constituent networks of the IPNs have been stabilized by sequential crosslinking. The mixing degree of the two networks and morphology of the resulted IPNs were studied. The measurements results show promising electromechanical behaviour for prepared IPNs.